European Union : Financial Sector Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
The recent financial crises have underscored the need for the European Union (EU) to take a regional approach to financial stability. Preserving financial stability in such an environment requires a supranational oversight framework. Progress has been made toward stronger pan-European approaches. Moving banks and sovereigns jointly to safety is essential. Bank recovery and resolution and harmonization are essential. The focus of this Financial Sector Stability assessment is on supranational institutions.